The Challenge of Differing Perspectives Surrounding Grades in the Assessment Education of Pre Service Teachers - Mitton Kukner, Jennifer; Munroe, Elizabeth; Graham, Deborah (Canadian Journal of Higher Education, 2015)
In this paper we describe the challenges we experience teaching an assessment course to pre-service teachers, as part of their studies in a bachelor of education program. As we teach the course, our intent is to explicitly model assessment practices that reflect a philosophy of success for all, rather than sort and rank. Rather than ranking students by achievement, our goal is to model how to tap into the learning potential of every student (Stiggins, 2005). Inquiring into moments that show how the teaching of a success for all philosophy is tension-filled in teacher education, we demonstrate the multiple and conflicting perspectives informing grades. We situate our discussion in the area of assessment in higher education and propose a series of actions, which may resonate with instructors in teacher education and higher education contexts.